Endothelial to Mesenchymal Transition – Purposeful versus Maladaptive Differentiation - Bischoff, Joyce (Circ Res, 2019)
EndMT is an intricate cellular differentiation process whereby endothelial cells detach and migrate away from the endothelium and, to varying extents, decrease endothelial properties and acquire mesenchymal features. First described in developing heart valves as an epithelial mesenchymal transformation, EndMT begins in response to an external signal, often transforming growth factor-β (TGFβ). The endothelial cells lose luminal-abluminal polarity, extend filopodia and migrate into extravascular space where they take up residence, in the case of heart valves, as valve interstitial cells. Properly controlled EndMT is essential for heart valve development: too little and valves fail to form; too much and the valves thicken and cannot close properly. EndMT appears to persist past embryonic development as endothelial cells expressing EndMT markers can be detected in vivo in adult ovine and human valves. In vitro, valve endothelial cells treated with TGFβ undergo robust EndMT; hence valve endothelial cells can serve as a prototype for revealing regulators of EndMT. Reactivation of EndMT in post-natal settings has emerged as a potential mechanism for adaptation to new physiologic settings and at the same time for maladaptive responses to disease(1). This is exemplified by EndMT in cardiac valves, which are lined with a specialized endothelium that originates from FLK1+ (a.k.a. VEGFR2+) progenitor cells in cardiac mesoderm, distinct from vascular endothelium(2). Although endocardial and vascular endothelium are molecularly similar(2), endocardial endothelial cells exhibit a distinct plasticity, which may provide valve endothelial cells with unique capabilities for adaptation and function over a lifetime.